METHODOLOGICAL PRINCIPLES OF DEVELOPING THE STRUCTURE OF A DICTIONARY ENTRY FOR A “DICTIONARY OF THE LANGUAGE OF ORAL FOLKLORE” (STABLE AND TEXTUAL AND FIGURATIVE UNITS) - Ruslan L. Serdeha (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
In Ukrainian linguistics, there is a need to develop methodological foundations and principles of lexicography of various linguistic facts present in the language of oral folk art. Folklore has always played an important role in preserving the identity of certain people. It contains the life experience of a certain ethnic group, accumulated during the life of many generations. Dictionaries have always been and will always be of great importance for the national progress and development of the national language, and the Dictionary of the Language Oral Folk Literature will contribute even more to both the preservation and popularization of the traditional cultural values of a particular nation. Thus, one of the urgent theoretical and practical tasks of national linguofolklore studies and Ukrainian linguistics in general, should be the problem of developing general principles and specific methodological foundations for lexicographic description of linguistic facts present in works of folklore, as well as the direct compilation of dictionaries of certain genres of oral folklore and the language of folklore in general. The purpose of the proposed study is to present certain methodological principles related to lexicography stable expressions, both phraseological expressions (idioms) and phraseological expressions (paremia – mainly sayings and proverbs, sometimes riddles, and even figurative constructions present in texts of oral folklore). In this article, we will present only a general scheme of a dictionary entry, suitable, in our opinion, for a more or less complete dictionary description of the entire linguistic richness of folklore, and will focus on the problem of parameterization of stable and textual-figurative units, which we plan to place either in the area outside the rhombus (phraseological units) or present as a separate structural element outside it (textual-figurative units). For this purpose, some stable and figurative expressions with the word “finger” from various collections of folklore have been identified. The attributive compounds present in folklore texts and claiming a certain, relatively speaking, stability are analyzed on the example of the lexeme “clothes”. Our research goal also involves outlining the concept of “phraseology of folklore” and clarifying its differences from the term “folklore phraseology” which is similar in meaning. We propose to approach the first concept as broadly as possible and not ignore the specific figurative constructions of folklore, which can also be included in the interpretive zone of a dictionary entry. This goal implies the use of the lexicographic method, which allows for the fullest possible representation of the entire arsenal of idiomatic and other textual and figurative means available in works of folklore, and also provides a relatively comprehensive picture of the phraseology of folklore, the language of oral folklore in general. It should be noted that this is a fairly reliable and effective method, the systematic and more or less complete implementation of which leads to noticeable achievements, such as the production of materials for a dictionary, or even to the emergence of a full-fledged lexicographic work. In addition, to reveal the meanings of the studied units of the language of oral folk art, we used the descriptive method, and to confirm the reliability of the given realizations of the semantics of stable compounds, the method of contextual analysis was used. In phraseology and phraseography, there are different approaches to defining the concept of phraseology. We strive to take the broadest possible approach to understanding this phenomenon. We propose to include in the register of the Dictionary of the Language of Oral Folk Literature a multifaceted material – not only semantically indivisible phraseological units (idioms) but also other phraseological units (phraseological unities and combinations, proverbs, sayings, comparative compounds, some term-like and free phrases and compounds that show a tendency to certain stability and regular reproduction, as well as textual and figurative units (extended metonymies and synecdoche’s, tautological and pleonastic constructions, euphemisms, periphrases, metaphorical expressions and compounds, epithets). The latter can be placed in a separate, special part of the dictionary entry devoted directly to the artistic and verbal means of folklore. Thus, the proposed dictionary, thanks to the involvement of constructions that have not undergone complete idiomology, will reflect to some extent the connecting possibilities of the register word. One-membered metaphors should be presented in an area directly related to interpretation because they form figurative meanings of the word. In the future, we plan to pay more attention to various textual and figurative units of folklore and present more or less detailed samples of the parameterization of the abovementioned oral means. Text-figurative units can also be displayed in a separate dictionary dedicated to various artistic and figurative verbal means of oral folk art or only one of them.